Implementasi Pendekatan Agama Untuk Meningkatkan Sikap Dan Kepedulian Terhadap Lingkungan (Studi Eksperimen dalam Pembelajaran IPS dengan Pendekatan Agama Islam Tentang Lingkungan Hidup) - Muhaimin Muhaimin (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2016)
The role of religion becomes very decisive in shaping the morality of human behavior that is more friendly to the environment. Religion becomes a source in guiding human behavior on the environment. Religious teachings are explored in the context of education to be one of the approaches, and learning resources to increase student awareness of the environment. The design of this quantitative research is done with a comparative approach pretest one-group-post test design to compare the students' attitude and concern for the environment before and after the implementation of learning by using religious approach on the environment. The subjects were 27 students of class V SDN Aengtabar 1 Bangkalan. Questionnaires were used to measure students' attitudes and concern for the environment. A statistical test of paired samples was used to analyze the data. The results showed a significant difference before and after the implementation of learning by using religious approach. Implemented learning could inspire more students to have an attitude and concern for the environment. It is these values that should be imparted to students early on with the foundations of the religion as a guideline to behave.